Non-aqueous electrolyte and secondary battery

By using structural formula 1 and structural formula 2 in the non-aqueous electrolyte in lithium iron phosphate batteries, the problem of insufficient cycle performance and low-temperature discharge capacity of the battery is solved, and higher cycle life and low-temperature performance are achieved.

CN119542543AActive Publication Date: 2025-02-28SHENZHEN CAPCHEM TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510106551.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

Lithium iron phosphate batteries have problems with insufficient circulation performance and low-temperature discharge capacity.

Method used

A nonaqueous electrolyte solution is provided, which comprises a nonaque organic solvent, an electrolyte salt and an additive, wherein the additives include specific compounds, Formula 1 and Formula 2, which open rings in advance during the battery formation stage to form an optimized solid electrolyte interface mask (SEI), thereby improving the cycle life and low temperature performance of the battery.

Benefits of technology

By optimizing the film formation quality of the SEI film, the internal resistance growth during the long cycle of the battery is delayed, the capacity release of the battery in a low temperature environment is improved, and the cycle life under normal temperature cycle is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542543A_ABST
    Figure CN119542543A_ABST
Patent Text Reader

Abstract

In order to solve the problem that an existing lithium iron phosphate battery is insufficient in cycle performance and low-temperature discharge capacity, the invention provides a non-aqueous electrolyte and a battery, the non-aqueous electrolyte comprises a non-aqueous organic solvent, an electrolyte salt and an additive, and the additive comprises a compound as shown in a structural formula 1 and a compound as shown in a structural formula 2: # imgabs 0 # and # imgabs 1 #. The non-aqueous electrolyte is detected by a liquid chromatography-mass spectrometer (LC-MS), and the non-aqueous electrolyte has a characteristic peak at the retention time of 1.55 + / -0.1 min. The non-aqueous electrolyte provided by the invention can delay the internal resistance increase in the long cycle process of the battery and improve the capacity release of the battery in a low-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy storage electronic components, and in particular relates to a non-aqueous electrolyte and a secondary battery. Background Art

[0002] In recent years, as the application technology of secondary batteries has gradually matured, the demand for electric vehicles and large-scale energy storage markets has exploded. Lithium iron phosphate cathode materials belong to the olivine-type stable structure, with the advantages of stable performance, environmental friendliness, low cost, safety and reliability, and are widely used in energy storage lithium-ion batteries. Therefore, how to maintain the energy density of lithium iron phosphate batteries while improving the cycle life has always been a key technical issue for researchers.

[0003] From a technical perspective, the core of lithium-ion battery long-cycle technology is to adjust and optimize the electrochemical stability of the solid electrolyte interface (SEI) through electrolyte design. The SEI formed by conventional chemical systems has defects and continuously dissolves and reorganizes during the charging and discharging process, which not only makes the interface film thicker and increases impedance, but also consumes active substances and causes capacity decay. In addition, the poor low-temperature discharge capability of lithium iron phosphate batteries used in electric vehicles has also been criticized by consumers. Summary of the invention

[0004] In view of the problems of insufficient cycle performance and low-temperature discharge capacity of existing lithium iron phosphate batteries, the present invention provides a non-aqueous electrolyte and a secondary battery.

[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a non-aqueous electrolyte, comprising a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive comprises a compound represented by structural formula 1 and a compound represented by structural formula 2: ; Structural formula 1 Wherein, n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1 and R2 may be the same. are interconnected to form a ring or not, and R1 and R2 are not hydrogen at the same time; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-C12 alkenylene, substituted or unsubstituted C2-C12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, and R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; ; Wherein, R4 is selected from substituted or unsubstituted C1-C6 alkylene, substituted or unsubstituted C2-C6 alkenylene, and when R4 is substituted, the substituent is C1-C5 alkyl, C1-C5 haloalkyl, C2-C5 alkenyl, C2-C5 haloalkenyl or halogen; The non-aqueous electrolyte is detected by liquid chromatography-mass spectrometry (LC-MS) and has a characteristic peak at a retention time of 1.55±0.1 min.

[0006] Optionally, in the compound represented by the structural formula 1, R1 is selected from hydrogen, and R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.

[0007] Optionally, in the compound shown in structural formula 1, R1 and R2 are each independently selected from a substituted or unsubstituted C1-C12 alkyl, a substituted or unsubstituted C2-C12 alkenyl, a substituted or unsubstituted C2-C12 alkynyl, or a substituted or unsubstituted C6-C20 aryl.

[0008] Optionally, in the compound represented by structural formula 1, R1 is selected from R2 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.

[0009] Optionally, in the compound represented by structural formula 1, R1 is selected from , where R 12R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.

[0010] Optionally, the compound represented by structural formula 1 includes one or more of the following compounds: and / or, The compound represented by the structural formula 2 includes one or more of the following compounds: .

[0011] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by structural formula 1 is 0.001% to 0.5%; and / or Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by structural formula 2 is 0.01% to 2%; and / or The mass ratio of the compound represented by the structural formula 2 to the compound represented by the structural formula 1 is 1-15.

[0012] Optionally, the additive further comprises at least one of sultone compounds, cyclic carbonate compounds, phosphate compounds, nitrile compounds, lithium salt additives or alkane compounds; and / or The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propylene sultone and methylene disulfonate; and / or The cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate or the compound shown in structural formula 3: ; In the structural formula 3, R 21 , R 22 , R 23 , R24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or The phosphate compound includes a compound shown in structural formula 4: ; In the structural formula 4, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, a C6-C12 aryl group, a C6-C12 halogenated aryl group, a -Si(C m H 2m+1 )3, m is a natural number from 1 to 3; and / or The nitrile compound comprises at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile; and / or The lithium salt additive includes at least one of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium tetrafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylsulfonyl imide, lithium bispentafluoroethylsulfonyl imide, lithium trifluoromethanesulfonate, lithium monofluorosulfonate, lithium trioxalate phosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium dicyanamide or a lower aliphatic lithium carboxylate having 4 or less carbon atoms; and / or The alkane compound includes at least one of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane and perfluoro(ethylcyclohexane).

[0013] Optionally, the non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.

[0014] In another aspect, the present invention provides a secondary battery comprising a positive electrode, a negative electrode and the non-aqueous electrolyte as described above; The positive electrode includes a positive electrode material layer, and the mass fraction of iron in the positive electrode material layer is greater than or equal to 17.7%.

[0015] According to the non-aqueous electrolyte provided by the present invention, the compound shown in structural formula 1 and the compound shown in structural formula 2 are added as additives, wherein the compound shown in structural formula 2 has a cyclic sulfate structure, and its decomposition product on the surface of the negative electrode will form a solid electrolyte interface film (SEI) containing Li2SO4 and ROSO3Li on the surface of the negative electrode. The SEI film can block the direct contact between the non-aqueous electrolyte and the negative electrode, avoid the continuous decomposition of the non-aqueous electrolyte at the negative electrode interface, and is beneficial to reduce the battery impedance and improve the battery cycle life. However, the increase in the ROSO3Li content will affect the stability of the SEI film, resulting in the battery cycle process. Impedance growth. In this regard, the inventors have found through extensive research that further adding the compound shown in Structural Formula 1 to the non-aqueous electrolyte containing the compound shown in Structural Formula 2 will induce the compound shown in Structural Formula 2 to open the ring in advance during the battery formation stage to form a specific species (related to the characteristic peak with a retention time of 1.55min±0.1min in the LC-MS specific conditions detection). This specific species takes precedence over other additives in film formation to form a SEI film with a relatively high Li2SO4 content and a relatively low ROSO3Li content, thereby delaying the internal resistance growth of the battery during long cycling and improving the capacity release of the battery in a low temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the detection result of the non-aqueous electrolyte provided in Example 1 of the present invention by the liquid chromatography-mass spectrometer (LC-MS); Figure 2 This is the detection result of the non-aqueous electrolyte provided in Comparative Example 15 of the present invention using a liquid chromatography-mass spectrometer (LC-MS). DETAILED DESCRIPTION

[0017] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0018] An embodiment of the present invention provides a non-aqueous electrolyte, including a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive includes a compound shown in Structural Formula 1 and a compound shown in Structural Formula 2: ; Wherein, n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1 and R2 may be the same. are interconnected to form a ring or not, and R1 and R2 are not hydrogen at the same time; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-C12 alkenylene, substituted or unsubstituted C2-C12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, and R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; ; Wherein, R4 is selected from substituted or unsubstituted C1-C6 alkylene, substituted or unsubstituted C2-C6 alkenylene, and when R4 is substituted, the substituent is C1-C5 alkyl, C1-C5 haloalkyl, C2-C5 alkenyl, C2-C5 haloalkenyl or halogen; The non-aqueous electrolyte is detected by liquid chromatography-mass spectrometry (LC-MS) and has a characteristic peak at a retention time of 1.55±0.1 min.

[0019] The compound shown in structural formula 1 and the compound shown in structural formula 2 are added as additives to the non-aqueous electrolyte, wherein the compound shown in structural formula 2 has a cyclic sulfate structure, and its decomposition product on the surface of the negative electrode will form a solid electrolyte interface film (SEI) containing Li2SO4 and ROSO3Li on the surface of the negative electrode. The SEI film can block the direct contact between the non-aqueous electrolyte and the negative electrode, avoid the continuous decomposition of the non-aqueous electrolyte at the negative electrode interface, and is beneficial to reduce the battery impedance and improve the battery cycle life. However, the increase in the ROSO3Li content will affect the stability of the SEI film, resulting in an increase in the impedance during the battery cycle. In this regard, the inventors have found through extensive research that further adding the compound of structural formula 1 to the non-aqueous electrolyte containing the compound of structural formula 2 will induce the compound of structural formula 2 to open the ring in advance during the battery formation stage to form a specific species (related to the characteristic peak with a retention time of 1.55min±0.1min in the LC-MS specific conditions detection). The specific species takes precedence over other additives in film formation to form a SEI film with a relatively high Li2SO4 content and a relatively low ROSO3Li content, thereby delaying the internal resistance growth of the battery during long cycle and improving the capacity release of the battery in a low temperature environment.

[0020] In some embodiments, the model of the LC-MS is Waters ACQUITY UPLC / Xevo G2-XS QtofMS, and the chromatographic conditions are: using a Waters T3 chromatographic column, a column temperature of 35-40°C, a mobile phase of a mixed solution of 40% water and 60% acetonitrile, and a mobile phase flow rate of 0.2-0.3 mL / min.

[0021] In the description of the present invention, the term "C1-C12 alkyl" includes straight-chain alkyl, branched-chain alkyl and cycloalkyl. Similarly, the term "C2-C12 alkenyl" includes straight-chain alkenyl, branched-chain alkenyl and cycloalkenyl. The term "C2-C12 alkynyl" includes straight-chain alkynyl, branched-chain alkynyl and cycloalkynyl. The term "C1-C12 alkylene" includes straight-chain alkylene, branched-chain alkylene and cycloalkylene. The term "C2-C12 alkenylene" includes straight-chain alkenylene, branched-chain alkenylene and cycloalkenylene. The term "C2-C12 alkynylene" includes straight-chain alkynylene, branched-chain alkynylene and cycloalkynylene.

[0022] In the description of the present invention, the term "C1-C12 acyl group" should be understood in a broad sense. Specifically, it can be understood that a single or multiple carbon atoms in a C1-C12 alkyl group are replaced by a carbonyl group. The position of the substituted carbon atom is not particularly limited. In a preferred embodiment, the C1-C12 acyl group is selected from , where R 14 and R 15 Each is independently selected from a single bond or a C1-C11 alkyl group.

[0023] In the description of the present invention, the term "C2-C12 alkoxy acyl" should be understood in a broad sense. Specifically, it can be understood that a single or multiple carbon atoms in a C2-C12 alkyl group are replaced by an ester group. The position of the substituted carbon atom is not particularly limited. In a preferred embodiment, the C2-C12 alkoxyacyl group is selected from , where R 16 is selected from a single bond or a C1-C11 alkyl group, R 17 An alkyl group selected from C1-C11.

[0024] In the description of the present invention, the term "C2-C12 ether group" should be understood in a broad sense. Specifically, it can be understood as a C2-C12 alkyl group connecting two adjacent carbon atoms. The number of oxygen atoms in the obtained group may be single or multiple.

[0025] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from hydrogen, R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.

[0026] At this time, the compound shown in the structural formula 1 is a hydroperoxide or an organic peracid. When the compound shown in the structural formula 1 is a hydroperoxide or an organic peracid, it has a higher oxygen content, which can remove reducing impurities in the electrolyte in advance, reduce the amount of gas produced during formation, improve the first coulomb efficiency, and increase the initial discharge capacity of the secondary battery.

[0027] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .

[0028] In some embodiments, in the compound represented by structural formula 1, R1 and R2 are each independently selected from a substituted or unsubstituted C1-C12 alkyl, a substituted or unsubstituted C2-C12 alkenyl, a substituted or unsubstituted C2-C12 alkynyl, or a substituted or unsubstituted C6-C20 aryl.

[0029] At this time, the compound shown in the structural formula 1 is a dialkyl peroxide. When the compound shown in the structural formula 1 is a dialkyl peroxide, the co-embedding of solvent molecules can be suppressed, thereby improving the interface compatibility between the electrolyte and the negative electrode.

[0030] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .

[0031] In some embodiments, in the compound represented by structural formula 1, R1 is selected from R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.

[0032] In some embodiments, in the compound represented by structural formula 1, R1 is selected from ; R2 is selected from , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.

[0033] At this time, the compound shown in the structural formula 1 is a diacyl peroxide. When the compound shown in the structural formula 1 is a diacyl peroxide, in addition to having the characteristics of improving the battery cycle life, it can also decompose to form inert carbon dioxide to dilute the explosion limit of the combustible gas when the battery is thermally runaway, which is beneficial to improving the battery safety performance.

[0034] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .

[0035] In some embodiments, in the compound represented by structural formula 1, R1 is selected from R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.

[0036] At this time, the compound shown in the structural formula 1 is a peroxy acid ester. When the compound shown in the structural formula 1 is a peroxy acid ester, the wettability of the electrolyte to the electrode can be improved, the ohmic internal resistance of the battery can be reduced, and the discharge performance of the battery can be improved.

[0037] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .

[0038] In some embodiments, in the compound represented by structural formula 1, R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.

[0039] At this time, the compound shown in the structural formula 1 is a peroxycarbonate or a peroxydicarbonate. When the compound shown in the structural formula 1 is a peroxycarbonate or a peroxydicarbonate, it has the effect of promoting the solvation of lithium ions and improving the lithium diffusion performance inside the battery.

[0040] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .

[0041] In some embodiments, the compound represented by structural formula 1 includes one or more of the following compounds: .

[0042] In some embodiments, the compound represented by structural formula 2 includes one or more of the following compounds: .

[0043] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by Structural Formula 1 is 0.001% to 0.5%.

[0044] In a specific embodiment, based on the total mass of the non-aqueous electrolyte as 100%, the mass percentage of the compound represented by Structural Formula 1 can be 0.001%, 0.002%, 0.005%, 0.008%, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.28%, 0.3%, 0.32%, 0.34%, 0.35%, 0.38%, 0.4%, 0.42%, 0.44%, 0.45%, 0.48%, 0.5% or a range consisting of any two of these values.

[0045] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by the structural formula 1 is 0.001% to 0.2%.

[0046] The compound shown in the structural formula 1 is used to promote the early ring opening of the compound shown in the structural formula 2 before the battery is formed, forming specific species to promote the increase of the Li2SO4 content in the SEI film, thereby improving the stability of the SEI film. When the mass percentage of the compound shown in the structural formula 1 is too low, it is difficult to substantially improve the film formation quality of the SEI film; when the mass percentage of the compound shown in the structural formula 1 is too high, the probability of side reactions in the electrolyte is increased, which is not conducive to the improvement of the cycle performance of the non-aqueous electrolyte.

[0047] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by Structural Formula 2 is 0.01% to 2%.

[0048] In a specific embodiment, based on the total mass of the non-aqueous electrolyte as 100%, the mass percentage of the compound represented by Structural Formula 2 can be 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.18%, 0.2% or a range consisting of any two of these values.

[0049] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by Structural Formula 2 is 0.01% to 1%.

[0050] The compound shown in Structural Formula 2 is used as the main film-forming additive for the negative electrode surface film formation, and its content affects the compactness of the SEI film on the negative electrode surface; if the content of the compound shown in Structural Formula 2 is too low, it is difficult to form a SEI film with high ionic conductivity at the negative electrode interface, which is not conducive to the release of low-temperature capacity; if the content of the compound shown in Structural Formula 2 is too high, it will cause the film thickness on the negative electrode surface to be too large, thereby increasing the impedance of the secondary battery.

[0051] In some embodiments, the mass ratio of the compound represented by the structural formula 2 to the compound represented by the structural formula 1 is 1 to 15. This helps to further improve the cycle life and low temperature performance of the battery.

[0052] In a specific embodiment, the mass ratio of the compound represented by Structural Formula 2 to the compound represented by Structural Formula 1 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or a range consisting of any two of these values.

[0053] In a preferred embodiment, the mass ratio of the compound represented by Structural Formula 2 to the compound represented by Structural Formula 1 is 1-10.

[0054] The inventors have found through extensive research that when the mass ratio of the compound represented by Structural Formula 2 to the compound represented by Structural Formula 1 is in the range of 1 to 15, the compound represented by Structural Formula 2 and the compound represented by Structural Formula 1 have the best synergistic effect, which is beneficial to improving the cycle capacity retention rate and low-temperature discharge performance of the battery.

[0055] It should be emphasized that the non-aqueous electrolyte provided in the present application is not a precursor of a gel electrolyte or a solid electrolyte, nor is it suitable as a precursor of a gel electrolyte or a solid electrolyte. The reason is that the improvement of the electrochemical performance of the secondary battery in the present application requires the compounds shown in Structural Formula 1 and the compounds shown in Structural Formula 2 to participate in the formation of the solid electrolyte interface film (SEI) on the negative electrode surface during the battery charge and discharge formation stage, and the compounds shown in Structural Formula 1 and the compounds shown in Structural Formula 2 remaining in the electrolyte to continuously repair the damaged solid electrolyte interface film (SEI) during the long-term cycle of the battery. As a precursor of a gel electrolyte or a solid electrolyte, there is a polymerization operation to form a gel electrolyte before the battery charge and discharge formation. In the polymerization operation, the organic peroxide shown in Structural Formula 1 reacts with the polymerizable monomer as an initiator, resulting in the consumption of the compound shown in Structural Formula 1, and thus cannot play a corresponding role in the charge and discharge formation and the battery charge and discharge cycle process.

[0056] In some embodiments, the non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.

[0057] In some embodiments, the polymerizable monomers include one or more of acrylate monomers (such as methyl acrylate, ethyl acrylate, butyl acrylate), acrylamide monomers (such as acrylamide, N,N'-methylenebisacrylamide), vinyl compound monomers (such as polyvinyl alcohol, vinyl pyrrolidone, vinyl imidazole), epoxy resin monomers (such as bisphenol A epoxy resin), polyethylene oxide monomers, polyacrylonitrile monomers, and siloxane monomers.

[0058] In some embodiments, the non-aqueous electrolyte does not undergo polymerization reaction under light or heating conditions.

[0059] In some embodiments, the non-aqueous electrolyte is in liquid state after formation.

[0060] In some embodiments, the additive further includes at least one of sultone compounds, cyclic carbonate compounds, phosphate compounds, nitrile compounds, lithium salt additives or alkane compounds.

[0061] In some embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propene sultone, and methylene disulfonate.

[0062] In some embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate, or a compound shown in Structural Formula 3: ; In the structural formula 3, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group.

[0063] In some embodiments, the phosphate compound includes a compound shown in structural formula 4: ; In the structural formula 4, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, a C6-C12 aryl group, a C6-C12 halogenated aryl group, a -Si(C m H 2m+1 )3, m is a natural number from 1 to 3.

[0065] In a preferred embodiment, the phosphate compound shown in the structural formula 4 can be at least one of triphenyl phosphate, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.

[0066] In some embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, and sebacononitrile.

[0067] In some embodiments, the lithium salt additive includes at least one of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium tetrafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylsulfonyl imide, lithium bispentafluoroethylsulfonyl imide, lithium trifluoromethanesulfonate, lithium monofluorosulfonate, lithium trioxalate phosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium dicyanamide, or a lower aliphatic lithium carboxylate having 4 or less carbon atoms.

[0068] In some embodiments, the alkane compound includes at least one of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane and perfluoro(ethylcyclohexane).

[0069] In other embodiments, the additives may also include other additives that can improve battery performance: for example, additives that enhance battery safety performance, such as flame retardant additives such as fluorophosphates and cyclophosphazenes, or overcharge prevention additives such as tert-amylbenzene and tert-butylbenzene.

[0070] It should be noted that, unless otherwise specified, in general, the content of any one of the optional substances in the additives in the non-aqueous electrolyte is less than 10%, preferably, the content is 0.01-5%, and more preferably, the content is 0.1%~2%. Specifically, the content of any one of the optional substances in the additives can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10% or a range consisting of any two of these values.

[0071] In some embodiments, the additive includes fluoroethylene carbonate, and based on the total mass of the non-aqueous electrolyte being 100%, the content of the fluoroethylene carbonate is 0.01% to 30%.

[0072] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the non-aqueous organic solvent is 65% to 90%.

[0073] Specifically, based on the total mass of the non-aqueous electrolyte as 100%, the mass content of the non-aqueous organic solvent can be 65%, 68%, 71%, 74%, 76%, 78%, 79%, 80%, 81.5%, 82%, 84%, 85%, 86%, 87%, 89%, 90% or a range consisting of any two of these values.

[0074] In some embodiments, the non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent, and a sulfone solvent.

[0075] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, preferably a chain ether with 3 to 10 carbon atoms and a cyclic ether with 3 to 6 carbon atoms. The cyclic ether may be, but is not limited to, at least one of 1,3-dioxolane, 1,4-dioxolane, crown ether, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; the chain ether may be, but is not limited to, dimethoxymethane, diethoxymethane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether. Since the chain ether has a high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ionic conductivity, are particularly preferred. The ether compound can be used alone or in any combination and ratio. The content of the ether compound is not particularly limited and is arbitrary within the range that does not significantly damage the effect of the high-density lithium-ion battery of the present invention. The volume ratio is usually 1% or more, preferably 2% or more, and more preferably 3% or more, based on the volume ratio of the non-aqueous solvent being 100%. In addition, the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less.

[0076] In some embodiments, the nitrile solvent may specifically be but is not limited to at least one of acetonitrile, glutaronitrile, and malononitrile.

[0077] In some embodiments, the carbonate solvent includes a cyclic carbonate or a chain carbonate, and the cyclic carbonate may be, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC); the chain carbonate may be, but is not limited to, at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC). The content of the cyclic carbonate is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention, but when one is used alone, the lower limit of its content is usually 3% or more by volume, preferably 5% or more by volume, relative to the total amount of solvent in the non-aqueous electrolyte. By setting this range, the decrease in conductivity due to the decrease in the dielectric constant of the non-aqueous electrolyte can be avoided, and it is easy to make the large current discharge characteristics, stability relative to the negative electrode, and cycle characteristics of the non-aqueous electrolyte battery reach a good range. In addition, the upper limit is usually 90% or less by volume, preferably 85% or less by volume, and more preferably 80% or less by volume. By setting this scope, the oxidation / reduction tolerance of nonaqueous electrolyte can be improved, thus contribute to the stability during high temperature storage. The content of linear carbonate is not particularly limited, and relative to the total amount of solvent of nonaqueous electrolyte, it is usually more than 15% by volume, preferably more than 20% by volume, and more preferably more than 25% by volume. In addition, usually the volume ratio is less than 90%, preferably less than 85% by volume, and more preferably less than 80% by volume. By making the content of linear carbonate in the above-mentioned scope, it is easy to make the viscosity of nonaqueous electrolyte reach appropriate range, suppress the reduction of ionic conductivity, and then contribute to make the output characteristics of nonaqueous electrolyte battery reach good scope. When two or more linear carbonates are used in combination, the total amount of linear carbonate is made to meet the above-mentioned scope.

[0078] In certain embodiments, it is also possible to preferably use chain carbonates with fluorine atoms (hereinafter referred to as "fluorinated chain carbonates"). The number of fluorine atoms possessed by the fluorinated chain carbonate is not particularly limited as long as it is more than 1, but is generally less than 6, preferably less than 4. When the fluorinated chain carbonate has a plurality of fluorine atoms, these fluorine atoms can be bonded to the same carbon or to different carbons. As the fluorinated chain carbonate, fluorinated dimethyl carbonate derivatives, fluorinated ethyl methyl carbonate derivatives, fluorinated diethyl carbonate derivatives, etc. can be listed.

[0079] Carboxylate solvents include cyclic carboxylate and / or chain carbonate. Examples of cyclic carboxylate include at least one of γ-butyrolactone, γ-valerolactone, and δ-valerolactone. Examples of chain carbonate include at least one of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, and butyl propionate.

[0080] In some embodiments, the sulfone solvent includes a cyclic sulfone and a chain sulfone. Preferably, in the case of a cyclic sulfone, it is usually a compound with 3 to 6 carbon atoms, preferably 3 to 5 carbon atoms, and in the case of a chain sulfone, it is usually a compound with 2 to 6 carbon atoms, preferably 2 to 5 carbon atoms. The content of the sulfone solvent is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention. Relative to the total amount of solvent of the non-aqueous electrolyte, the volume ratio is usually 0.3% or more, preferably 0.5% or more, and more preferably 1% or more. In addition, the volume ratio is usually 40% or less, preferably 35% or less, and more preferably 30% or less. In the case of using two or more sulfone solvents in combination, the total amount of the sulfone solvent is sufficient to meet the above range. When the content of the sulfone solvent is within the above range, a non-aqueous electrolyte with excellent high temperature storage stability tends to be obtained.

[0081] In a preferred embodiment, the non-aqueous organic solvent comprises a mixture of cyclic carbonate and linear carbonate.

[0082] In some embodiments, the electrolyte salt is selected from lithium salts, including LiPF6, LiODFP, LiODFB, LiBOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiClO4, LiAlCl4, LiCF3SO3, LiSO3F, Li2B 10 Cl 10 , lithium chloroborane, lithium trioxalophosphate, a lithium lower aliphatic carboxylate having 4 or less carbon atoms, or at least one of lithium tetraphenylborate.

[0083] In some embodiments, the concentration of the lithium salt in the non-aqueous electrolyte is 0.1 mol / L to 4 mol / L. In a preferred embodiment, the concentration of the lithium salt in the non-aqueous electrolyte is 0.5 mol / L to 2.5 mol / L. Specifically, in the non-aqueous electrolyte, the concentration of the lithium salt can be 0.5mol / L, 0.55mol / L, 0.6mol / L, 0.65mol / L, 0.7mol / L, 0.8mol / L, 0.85mol / L, 0.9mol / L, 0.95mol / L, 1.0mol / L, 1.1mol / L, 1.15mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.45mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L, 2.0mol / L, 2.1mol / L, 2.2mol / L, 2.3mol / L, 2.4mol / L, 2.5mol / L or a range consisting of any two of these values.

[0084] Another embodiment of the present invention provides a secondary battery including a positive electrode, a negative electrode, and the non-aqueous electrolyte as described above.

[0085] In some embodiments, the secondary battery is a lithium-ion battery.

[0086] In some embodiments, the positive electrode includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel oxide (such as lithium nickel oxide), lithium manganese oxide (such as spinel lithium manganese oxide, layered structure lithium manganese oxide, etc.), lithium iron phosphate, lithium manganese phosphate, lithium cobalt oxide, and one or more of their doped / coated modified compounds. Preferably, the positive electrode active material includes LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z At least one of O2, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.

[0087] In a preferred embodiment, the mass fraction of iron in the positive electrode material layer is greater than or equal to 17.7%. When the mass fraction of iron in the positive electrode material layer satisfies the above range, the positive electrode material layer has a higher gram capacity, thereby effectively improving the energy density of the battery, and the charging cut-off voltage of the battery can reach 3.8V, with a higher discharge platform, and shows good cycle stability under the conventional voltage window; and because iron is relatively abundant and low in price worldwide, compared with rare and expensive metals such as cobalt, nickel, and manganese, the use of the aforementioned positive active material helps to reduce costs and reduce dependence on limited resources.

[0088] In a more preferred embodiment, the positive electrode active material includes LiFe 1-x’ M' x’ PO4. The compound shown in the structural formula 1 and the compound shown in the structural formula 2 have good synergistic effects, significantly reduce the dissolution of iron ions in the battery, effectively reduce the SEI film rupture and reorganization caused by the deposition of iron ions on the SEI film surface, and effectively improve the cycle performance of the battery.

[0089] In some specific embodiments, the positive electrode active material may include LiCoO2, LiFePO4, LiFe 0.4 Mn 0.6 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2、LiNi 0.5 Co 0.2 Al 0.3 One or more of O2.

[0090] In some embodiments, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer.

[0091] The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.

[0092] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.

[0093] In some embodiments, the positive electrode current collector includes a metal material that can conduct electrons. Preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.

[0094] In some embodiments, the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy.

[0095] In a more preferred embodiment, the negative electrode active material includes at least one of graphite, hard carbon, soft carbon, graphene, and silicon-carbon composite materials.

[0096] In some embodiments, the silicon material is one or more of silicon nanoparticles, silicon nanowires, silicon nanotubes, silicon thin films, 3D porous silicon, and hollow porous silicon.

[0097] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer covers the surface of the negative electrode current collector. The negative electrode current collector comprises a metal material that can conduct electrons, preferably, the negative electrode current collector comprises at least one of Al, Ni, tin, copper, and stainless steel, and in a more preferred embodiment, the negative electrode current collector is selected from copper foil.

[0098] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are blended to obtain the negative electrode material layer.

[0099] The negative electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.

[0100] The negative electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.

[0101] In some embodiments, the secondary battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.

[0102] The diaphragm may be an existing conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.

[0103] The present invention is further described below by way of examples.

[0104] Table 1

[0105] Among them, VC is vinylene carbonate, FEC is fluoroethylene carbonate, MMDS is methylene methanedisulfonate, and LiDFP is lithium difluorophosphate.

[0106] Example 1 This example is used to illustrate the preparation method of the lithium ion battery disclosed in the present invention, which includes the following steps: (1) Preparation of non-aqueous electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed at a mass ratio of EC:PC:DMC:EMC=5:6:8, and then 1 mol / L lithium hexafluorophosphate (LiPF6) is added as an electrolyte salt. Based on the total weight of the non-aqueous electrolyte being 100%, additives are added in order in the mass percentages shown in Table 1.

[0107] (2) Battery filling and formation: In a glove box with a water content of <10ppm and an oxygen content of <50ppm, the prepared electrolyte was injected into a dry battery cell with a positive electrode of lithium iron phosphate and a negative electrode of artificial graphite, wherein the mass fraction of iron in the positive electrode material layer was 34%. The battery was kept at a vacuum of 20kPa for 10min and allowed to stand at room temperature for one day after packaging.

[0108] Then, the first charge was conventionally formed according to the following steps: 0.05C constant current charging for 120 min, 0.1C constant current charging for 60 min, and 0.2C constant current charging for 60 min. After the formation, the battery was vacuumed, vented, sealed, and placed in a 45°C oven for one day. Then, the battery was further charged at 0.2C constant current to 3.65V, and constant voltage charged to 0.03C cutoff, to obtain a lithium iron phosphate / graphite battery.

[0109] Embodiments 2 to 23 Examples 2 to 23 are used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and include most of the operating steps in Example 1, except that: The mass content of each component in the electrolyte is shown in Table 1.

[0110] Comparative Examples 1 to 27 Comparative Examples 1 to 27 are used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and include most of the operating steps in Example 1, except that: The mass content of each component in the electrolyte is shown in Table 1.

[0111] Performance Testing 1. The electrolytes obtained in Example 1 and Comparative Example 15 were tested by liquid chromatography-mass spectrometry (LC-MS). The model of the LC-MS was Waters ACQUITY UPLC / Xevo G2-XS Qtof MS. The chromatographic conditions were: a Waters T3 column, a column temperature of 35-40°C, a mobile phase of a mixed solution of 40% water and 60% acetonitrile, and a mobile phase flow rate of 0.2-0.3 mL / min. The test results obtained are as follows: Figure 1 and Figure 2 shown.

[0112] Depend on Figure 1 and Figure 2 It can be seen from the test results that a characteristic peak appears at a retention time of 1.55 min in the spectrum obtained in Example 1, while the characteristic peak is not reflected in the spectrum of Comparative Example 15, indicating that the material composition of Example 1 is different from that of Comparative Example 15.

[0113] 2. The lithium-ion batteries prepared in the above examples and comparative examples were subjected to the following performance tests: 2.1. Battery cycle test at room temperature: The fresh battery after capacity division was placed in a constant temperature environment of 25℃, and after a short period of rest, it was charged to 3.65 V at a constant current and constant voltage of 1C, with a cut-off current of 0.05C. After a short period of rest, it was discharged to 2.5 V at a constant current of 1.5C, and the charge and discharge cycle was repeated for 2000 cycles. The discharge capacity of each cycle was recorded, and the capacity retention rate (%) = 2000th cycle discharge capacity / first cycle discharge capacity * 100%, and the cycle internal resistance growth rate (%) = (internal resistance after 2000 cycles - internal resistance after capacity division) / internal resistance after capacity division * 100%, and the average value between parallel samples was calculated.

[0114] 2.2. Battery low temperature discharge test: The fresh battery after capacity division is placed in a 25℃ constant temperature environment, and after a short period of time, it is charged to 3.65V at a constant current and voltage of 0.5C, with a cut-off current of 0.05C. Then it is transferred to a -20℃ constant temperature environment, and after being placed for 2 hours, it is discharged to 2.0V at a constant current of 0.5C. Calculate according to the following formula: Low temperature discharge efficiency (%) = low temperature discharge capacity / normal temperature charging capacity * 100%; (1) The test results obtained in Examples 1 to 21 and Comparative Examples 1 to 8 and 15 to 21 are entered in Table 2.

[0115] Table 2

[0116] It can be seen from the test results of Examples 1 to 21 and Comparative Examples 1 to 8 and 15 to 21 that, compared with the addition of the compound shown in Structural Formula 1 alone or the addition of the compound shown in Structural Formula 2 alone to the non-aqueous electrolyte in the comparative example, Examples 1 to 14 in which the compound shown in Structural Formula 1 is added simultaneously or the compound shown in Structural Formula 2 is added alone have significant improvements in improving the cycle capacity retention rate of the lithium-ion battery, low-temperature discharge efficiency and reducing the internal resistance growth rate, indicating that the compound shown in Structural Formula 1 and the compound shown in Structural Formula 2 can effectively improve the ion conduction efficiency of the SEI film in the negative electrode film formation stage of the battery formation. Specifically, the compound shown in Structural Formula 1 induces the compound shown in Structural Formula 2 to open the ring in advance in the battery formation stage to form a specific species, and the specific species forms a film before other additives to form a SEI film with a relatively high Li2SO4 content and a relatively low ROSO3Li content, thereby delaying the internal resistance growth during the long cycle of the battery, and improving the capacity release of the battery in a low temperature environment and extending the cycle life under normal temperature cycles.

[0117] It can be seen from the test results of Examples 1 to 21 that when the mass ratio of the compound represented by Structural Formula 2 to the compound represented by Structural Formula 1 is in the range of 1 to 15, it is beneficial to improve the cycle performance and low-temperature discharge performance of the battery. This indicates that there is a mutual coordination effect between the compound represented by Structural Formula 1 and the compound represented by Structural Formula 2. Therefore, when the contents of the two are in a synergistic state, it is beneficial to improve the electrochemical performance of the lithium-ion battery.

[0118] (2) The test results obtained in Examples 3, 22 to 27 and Comparative Examples 9 to 14, 22 to 27 are entered in Table 3.

[0119] Table 3

[0120] It can be seen from the test results of Examples 3, 22 to 27 and Comparative Examples 9 to 14, 22 to 27 that, compared with the comparative examples, when different compounds represented by structural formula 1 and different compounds represented by structural formula 2 are used as additives in each embodiment, the cycle performance and low temperature performance of the lithium ion battery are significantly improved, indicating that the compounds represented by different structural formula 1 and the compounds represented by different structural formula 2 have a common structure, that is, the compounds represented by different structural formula 1 have a common structure of a peroxide bond -OO-, and the compounds represented by different structural formula 2 have a common structure of a sulfate ring, and this structural commonality is associated with the synergistic effect between the two.

[0121] (3) The test results obtained in Examples 3, 28-30 are entered in Table 4.

[0122] Table 4

[0123] It can be seen from the test results of Examples 3 and 28 to 30 that in the electrolyte system of the present invention, further adding other additives (VC vinylene carbonate, FEC fluoroethylene carbonate, MMDS methylene disulfonate, LiDFP lithium difluorophosphate) is beneficial to further improve the cycle capacity retention rate of the lithium ion battery and reduce its low-temperature internal resistance growth, indicating that the improvement mechanism of other types of additives for battery performance is different from the coordination mechanism between the compound shown in Structural Formula 1 and the compound shown in Structural Formula 2, and can improve the performance of lithium ion batteries from different aspects.

[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A non-aqueous electrolyte, characterized in that: It includes a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive includes a compound shown in Structural Formula 1 and a compound shown in Structural Formula 2: ; Wherein, n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1 and R2 may be the same. are interconnected to form a ring or not, and R1 and R2 are not hydrogen at the same time; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-C12 alkenylene, substituted or unsubstituted C2-C12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, and R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; ; Wherein, R4 is selected from substituted or unsubstituted C1-C6 alkylene, substituted or unsubstituted C2-C6 alkenylene, and when R4 is substituted, the substituent is C1-C5 alkyl, C1-C5 haloalkyl, C2-C5 alkenyl, C2-C5 haloalkenyl or halogen; The non-aqueous electrolyte is detected by liquid chromatography-mass spectrometry (LC-MS) and has a characteristic peak at a retention time of 1.55±0.1 min.

2. The non-aqueous electrolyte according to claim 1, characterized in that In the compound represented by the structural formula 1, R1 is selected from hydrogen, R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.

3. The non-aqueous electrolyte according to claim 1, characterized in that In the compound represented by structural formula 1, R1 and R2 are each independently selected from a substituted or unsubstituted C1-C12 alkyl group, a substituted or unsubstituted C2-C12 alkenyl group, a substituted or unsubstituted C2-C12 alkynyl group, or a substituted or unsubstituted C6-C20 aryl group.

4. The non-aqueous electrolyte according to claim 1, characterized in that In the compound represented by the structural formula 1, R1 is selected from R2 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.

5. The non-aqueous electrolyte according to claim 1, characterized in that In the compound represented by the structural formula 1, R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.

6. The non-aqueous electrolyte according to claim 1, characterized in that The compound represented by the structural formula 1 includes one or more of the following compounds: and / or, The compound represented by the structural formula 2 includes one or more of the following compounds: 。 7. The non-aqueous electrolyte according to claim 1, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by the structural formula 1 is 0.001% to 0.5%; and / or Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage of the compound represented by structural formula 2 is 0.01% to 2%; and / or The mass ratio of the compound represented by the structural formula 2 to the compound represented by the structural formula 1 is 1-15.

8. The non-aqueous electrolyte according to claim 1, characterized in that The additive further comprises at least one of sultone compounds, cyclic carbonate compounds, phosphate compounds, nitrile compounds, lithium salt additives or alkane compounds; and / or The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propylene sultone and methylene disulfonate; and / or The cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate or the compound shown in structural formula 3: ; Structural formula 3 In the structural formula 3, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or The phosphate compound includes a compound shown in structural formula 4: ; In the structural formula 4, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, a C6-C12 aryl group, a C6-C12 halogenated aryl group, a -Si(C m H 2m+1 )3, m is a natural number from 1 to 3; and / or The nitrile compound comprises at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile; and / or The lithium salt additive includes at least one of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium tetrafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylsulfonyl imide, lithium bispentafluoroethylsulfonyl imide, lithium trifluoromethanesulfonate, lithium monofluorosulfonate, lithium trioxalate phosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium dicyanamide or a lower aliphatic lithium carboxylate having 4 or less carbon atoms; and / or The alkane compound includes at least one of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane and perfluoro(ethylcyclohexane).

9. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.

10. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the non-aqueous electrolyte as claimed in any one of claims 1 to 9.

11. The secondary battery according to claim 10, characterized in that: The positive electrode includes a positive electrode material layer, and the mass fraction of iron in the positive electrode material layer is greater than or equal to 17.7%.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte and lithium ion battery including same

    CN102610856A

  • Electrochemical cells comprising electrolyte additives, and methods for making and using the same

    CN104541388A

  • Non-aqueous electrolyte and lithium ion battery

    CN115207462A

  • Non-aqueous electrolyte and lithium ion battery thereof

    CN116845358A

  • Electrolyte for lithium cell and lithium cell containing the same

    CN1495961A